Kinerja Lingkungan, Manajemen Laba, Corporate Governance Dan Corporate Social Responsibility (CSR) - Dewi, Putu Purnama; Emi Eka Yanti, I Gusti Ayu (E-Jurnal Akuntansi; Vol 28 No 1 (2019)DO - 10.24843/EJA.2019.v28.i01.p22, 2019)
Research on the influence of environmental performance on corporate social responsibility is still rarely studied. However, the influence of earnings management and corporate governance on corporate social responsibility has been investigated. This study used  institutional ownership, managerial ownership, board of commissioners and audit committees as corporate governance’s proxy. This study aimed to investigate the influence of environmental performance, earnings management and corporate governance on corporate social responsibility by using mining companies that have been listed on the Indonesian stock exchange and are also registered with PROPER. In this study using multiple regression analysis method with 45 samples which showed the results of research that only environmental performance had an influence on corporate social responsibility, while earnings management, institutional ownership, managerial ownership, board of commissioners and audit committees did not affect corporate social responsibility. Keywords : Environmental performance, earnings management, corporate governance, corporate social responsibility .